Dharmagita; Seni Budaya Dalam Siar Agama Hindu - Yunitha Asri Diantary Ni Made; I Made Hartaka (Jnanasidanta, 2021)
The development of technology and information is able to bring changes in all lines of life. Humans have begun to become complacent about the easy and sophisticated life, so that the noble religious values are now not the main thing again. Humans are now busy looking for their existence, competing with their siblings for recognition, especially teenagers who are easily influenced by everything they consider fun, there needs to be an appropriate solution to minimize this, because humans are born to correct previous bad karma and in current lives. This needs an arrangement for oneself, society and the people to become human dharmics. Religious values must be packaged in such a way as to facilitate the spread of teachings in achieving the mission of dharma. Dharmagita as one of the cultural arts in Bali plays an important role in the mission of spreading Hinduism. Dharmagita in the development of mental spiritual religion and increase understanding of the values of religious teachings. Through understanding the practice of Dharmagita, it is possible to form the next generation to have quality sradha and devotional service while preserving the arts and culture in Bali.